Comportamiento De Los Créditos De Vivienda En Colombia Durante El Periodo De La Pandemia Covid-19 (2023)
In this work, a study was carried out whose purpose was to determine the impact of the COVID-19 pandemic on the housing mortgage portfolio (CHV - for its acronym in Spanish), the data were extracted from the annexes published by the national administrative department of statistics (DANE - for its acronym in Spanish), in Based on these data, different analyzes were carried out according to the type of housing and the type of credit, through tables and graphs it was possible to observe the behavior of mortgage loans at the national level. The results show the importance that social interest housing and housing leasing have been taking. Therefore, it is concluded that the COVID-19 pandemic did not reduce the housing mortgage portfolio, but it did transform it, giving greater importance to the most vulnerable sectors.